The association between sleep duration, respiratory symptoms, asthma, and COPD in adults - Ruan, Zhishen; Li, Dan; Cheng, Xiaomeng; Jin, Minyan; liu, Ying; Qiu, Zhanjun; Chen, Xianhai (Frontiers in Medicine, 2023)
Abstract Introduction: The association between sleep duration and cough, wheezing, and dyspnea was unclear. This research aimed to test this relationship. Methods: Research data were obtained from people who participated in the National Health and Nutrition Examination Survey (NHANES) from 2005-2012. We used weighted logistic regression analysis and fitted curves to explore the association between sleep and respiratory symptoms. In addition, we investigated the association between sleep duration, chronic obstructive pulmonary disease (COPD), and asthma. The stratified analysis is used to analyze inflection points and specific populations. Results: The 14742 subjects are weighted to reflect the 45,678,491 population across the United States. Weighted logistic regression and fitted curves show a U-shaped relationship between sleep duration and cough and dyspnea. This U-shaped relationship remained in people without COPD and asthma. The stratified analysis confirmed that sleep duration before 7.5 hours was negatively associated with cough (HR 0.80, 95% CI 0.73-0.87) and dyspnea (HR 0.82, 95% CI 0.77-0.88). In contrast, it was positively associated with cough and (HR 1.30, 95% CI 1.14-1.48) dyspnea (HR 1.12, 95% CI 1.00-1.26) when sleep duration was >7.5h. In addition, short sleep duration is associated with wheezing, asthma, and COPD. Conclusions: Both long and short sleep duration are associated with cough and dyspnea. And short sleep duration is also an independent risk factor for wheezing, asthma, and COPD. This finding provides new insights into the management of respiratory symptoms and diseases.